2019 Kansas State University Industrial Hemp Dual-Purpose and Fiber Trial - Jason Griffin; Kraig Roozeboom; Lucas Haag; Michael Shelton; Clint Wilson; Tami Myers (Kansas Agricultural Experiment Station Research Reports, 2020)
Hemp is a broad term used to describe the many varieties ofCannabis sativaL. that produce less than 0.3% tetrahydrocannabinol (THC). The crop is globally significant, but only recently allowed to be grown again in the United States. Varieties that have numerous industrial uses have been selected for improved fiber and grain production. However, there is no information available regarding adaptability or production of these varieties in Kansas. In 2019, Kansans were allowed to apply for research licenses to grow industrial hemp. It was assumed the crop would grow well throughout Kansas since there are wild remnant populations ofC. sativaflourishing at numerous locations across the state. However, controlled variety trials are necessary to determine which varieties are best adapted to the state. Currently, farmers must rely on information generated from other states with vastly different growing conditions than Kansas. Variety selection is vital in hemp production considering latitude (day length) and length of growing season influence planting time, number of days to harvest, and ultimately yield. The objective of this study was to evaluate commercially available varieties of industrial hemp in south central Kansas.
Keywords: Cannabis sativa; alternative crops; grain; seed oil